From ‘artifact’ to stage ‘performance’: A comparison of the romantic-nationalist and performative paradigms in folklore studies - Andalas, Eggy Fajar; Prawiroatmodjo, Sudibyo; Saktimulya, Sri Ratna; Indrastuti, Novi Siti Kussuji (Universitas Mulawarman, 2025)
The emergence of the text/context debate in folklore research has facilitated new interpretations of how researchers approach their objects. Folklore research focusing solely on